Concentration of Cranberry Juice by Osmotic Distillation Process - Saavedra-Fenoglio, A; Romero-Figueroa, J (Elsevier Ltd, 2014)
An osmotic distillation (OD) system was implemented to concentrate cranberry juice at laboratory scale. The experimental setup allows the circulation of cranberry juice (Vaccinium macrocarpon Ait.) and an osmotic agent with flow rates varying from 0.5 to 1.5 L min-1 at temperatures between 30 and 40 °C. The osmotic agent selected in this study was a concentrated CaCl2(aq) solution with concentrations ranged from 30% to 50% w/w. The transmembrane flux of water vapor was ranged between 0.25 and 1.21 L h-1 m-2. The comparative low content of TSS in cranberry juice allows obtaining fast water removal from 500 mL of juice, achieving concentrations from 8.6 to 48°Brix in 18 min. The total phenolic content was preserved after concentration. A mass transfer model was developed to explain the concentration kinetics of the juice. The solution simulations allow obtaining a maximum deviation of 32% between experimental and simulated values of transmembrane water flux. © 2014 Published by Elsevier Ltd.